Neuropsychological profile of young adults with spina bifida with or without hydrocephalus. Issue 8 (16th July 2004) - Iddon, J L; Morgan, D J R; Loveday, C; Sahakian, B J; Pickard, J D
Abstract : Objectives: To determine the relative impact of hydrocephalus and spinal dysraphism in young adults on intellectual and cognitive functioning. Sub-groups of patients with congenital hydrocephalus and/or spina bifida were assessed between 1995 and 2003. The entry criteria were that individuals should have (i) intact global function, (ii) average verbal intelligence (or above), and (iii) should not have clinical depression. There were three sub-groups: patients with hydrocephalus and spina bifida, patients with hydrocephalus without spina bifida, and patients with spina bifida without hydrocephalus. Methods: Patients were neuropsychologically assessed as part of their normal clinical assessment during their annual medical review. Each individual completed a screening battery assessing global functioning, verbal intelligence, and mood. In addition they completed additional tests including measures of emotional intelligence, memory, attention, and executive function. Results were analysed to compare the performance of the patient sub-groups and to compare them to a healthy control group. Results: Patients with hydrocephalus (with or without spina bifida) were significantly impaired on the vast majority of all test scores as compared to patients with spina bifida and healthy controls. They were particularly poor on measures assessing executive function. By contrast for patients with spina bifida with no associated hydrocephalus, the significant majority of all test scores fell within the average range or above. Conclusions: The neuropsychological profile of patients with hydrocephalus is one of relative impairment and this is so whether or not spina bifida is present. In spina bifida alone, in the absence of hydrocephalus, cognitive function is relatively spared.